2021
DOI: 10.2196/24724
|View full text |Cite
|
Sign up to set email alerts
|

Business Models of eHealth Interventions to Support Informal Caregivers of People With Dementia in the Netherlands: Analysis of Case Studies

Abstract: Background In academic research contexts, eHealth interventions for caregivers of people with dementia have shown ample evidence of effectiveness. However, they are rarely implemented in practice, and much can be learned from their counterparts (commercial, governmental, or other origins) that are already being used in practice. Objective This study aims to examine a sample of case studies of eHealth interventions to support informal caregivers of peopl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Most documents were excluded because they did not discuss the current reimbursement or financing pathways in place in the studied countries. We included 9 original research articles [ 11 , 20 , 44 - 50 ], 5 reviews [ 8 , 18 , 27 , 51 , 52 ], 4 conference abstracts [ 53 - 56 ], 18 gray literature sources [ 28 , 57 - 73 ], 3 reports [ 74 - 76 ], and 1 commentary [ 25 ]. In terms of country focus, 3 documents focused on Belgium [ 57 - 59 ], 8 on France [ 11 , 28 , 51 , 54 - 56 , 60 , 61 ], 6 on Germany [ 18 , 27 , 44 , 52 , 54 , 62 ], 3 on Israel [ 45 , 63 , 76 ], 4 on Italy [ 46 - 48 , 64 ], 5 on the Netherlands [ 8 , 20 , 49 , 65 , 75 ], 5 on Poland [ 50 , 66 - 68 , 74 ], 3 on Sweden [ 69 - 71 ], and 6 on the United Kingdom [ 28 , 53 , 54 , 56 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most documents were excluded because they did not discuss the current reimbursement or financing pathways in place in the studied countries. We included 9 original research articles [ 11 , 20 , 44 - 50 ], 5 reviews [ 8 , 18 , 27 , 51 , 52 ], 4 conference abstracts [ 53 - 56 ], 18 gray literature sources [ 28 , 57 - 73 ], 3 reports [ 74 - 76 ], and 1 commentary [ 25 ]. In terms of country focus, 3 documents focused on Belgium [ 57 - 59 ], 8 on France [ 11 , 28 , 51 , 54 - 56 , 60 , 61 ], 6 on Germany [ 18 , 27 , 44 , 52 , 54 , 62 ], 3 on Israel [ 45 , 63 , 76 ], 4 on Italy [ 46 - 48 , 64 ], 5 on the Netherlands [ 8 , 20 , 49 , 65 , 75 ], 5 on Poland [ 50 , 66 - 68 , 74 ], 3 on Sweden [ 69 - 71 ], and 6 on the United Kingdom [ 28 , 53 , 54 , 56 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some digital health solutions are made available through sponsorships from nongovernmental organizations (eg, Alzheimer Netherlands sponsoring 2 digital health apps for dementia) [ 8 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that guidance by a coach could be a valuable contribution to online interventions, as blended eHealth interventions (that is, eHealth interventions that combine online and offline support elements) for caregivers appear to be more effective than nonblended interventions [ 15 ]. Moreover, integrating eHealth interventions for caregivers of people with dementia into existing (dementia) care organizations is an important determinant of their sustained implementation success [ 40 ]. This approach would necessitate thorough training and monitoring of the implementing health care professionals, as research has shown that implementer self-efficacy and sense of ownership are important predictors of sustainable implementation of online interventions for caregivers of people with dementia [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inspiration for methods to evaluate (new functionalities to) eHealth interventions can be gained from industry, where many commercial platforms use real-time evaluations to gain feedback from users. These can include pop-ups, which ask the user to rate their experiences, or the launch of different versions of the same functionality in order to assess which of the 2 versions is more successful [ 40 ]. It is possible that the retrospective measurements used in this study could not capture the kinds of practical benefits (ie, increased time savings and positive interactions) that are highly important and ecologically valid for informal caregivers.…”
Section: Discussionmentioning
confidence: 99%